HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PENCEGAHAN HUMAN IMMUNODEFISIENCY VIRUS PADA IBU HAMIL DI PUSKESMAS SENTANI KABUPATEN JAYAPURA - Lestari, Tiyan Febriyani (Ensiklopedia Research and Community Service Review, 2025)
Abstract: Acquired Immune Deficiency Syndrome (AIDS) is a collection of symptoms of the disease caused by the Human Immunodeficiency Virus (HIV) which can be contagious and deadly. This virus attacks the human immune system (RI Ministry of Health, 2020). HIV infection in pregnant women in Indonesia is increasing from year to year, this is due to several factors, namely knowledge and family support for HIV prevention in pregnant women. The aim of this research is to determine the relationship between knowledge and family support on HIV prevention in pregnant women. The method used in this research is Correlation Analysis with a cross-sectional approach. The results of this research show a relationship between knowledge and HIV prevention in pregnant women with a p value of 0.009, and there is a relationship between family support and HIV prevention in pregnant women with a p value of 0.031. Conclusion: There is a relationship between knowledge and family support for HIV prevention in pregnant women at the Sentani Health Center.Keywords: HIV, AIDS, Pregnancy, Knowledge, Prevention